The Effect of Anonymous Peer Assessment on Writing Ability of the Eleventh Grade Students at SMK PGRI 1 Singaraja - A.P. Adhiyanti; A.A.I.N Marhaeni; I.P.I Kusuma (Journal of Psychology and Instruction, 2018)
This study aimed to investigate the effect of anonymous peer assessment on students’ writing ability. Quantitative approach was used in this study. Post-test only control group design was the design used in this experimental study. The post-test only control group design was designed to discover the purpose of this study which was to investigate the significant effect on writing ability between students who obtain feedback from anonymous peer assessment and students who obtain feedback from conventional assessment. The study was conducted at SMK PGRI 1 Singaraja. The eleventh grade students in Academic Year 2017/2018 were chosen as the population. The samples were 44 students from XI AP and XI UPW. The instruments used in this study were lesson plan, anonymous peer checklist, writing scoring rubric, and writing test. Writing scoring rubric and writing test were used to obtain the data through post-test while lesson plan and anonymous peer assessment were used during the treatment. The data then was analyzed by using SPSS 16. The results of the analysis show that (1) the mean score of the experimental group was 77.55 while the mean score of the control group was 68.77. (2) The t-observe was 3.892 and it exceeded the t-critical value which was 2.018. Therefore, based on the aforementioned results, it can be concluded that there was a significant difference on writing ability between the eleventh grade students who obtained feedback from anonymous peer assessment and those who obtained feedback from conventional assessment at SMK PGRI 1 Singaraja in academic year 2017/2018.